2020
DOI: 10.1016/j.cell.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Signaling Roles of CD3ε and Its Application in CAR-T Cell Therapy

Abstract: Highlights d The four types of CD3 signaling chains of TCR have functional diversity d CD3ε recruits Csk and p85 via its mono-phosphorylated ITAM and BRS motif respectively d Incorporation of CD3ε into 28Z CAR alters signaling to promote antitumor function d E28Z CAR-T cells have reduced cytokine production but enhanced persistence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 70 publications
2
93
0
Order By: Relevance
“…The molecular mechanism underlying the distinction between the cytolytic and pro‐inflammatory function of T cells is not fully understood. However, a recent study revealed that the alternation of TCR signalling via modulating CD3 subunits can maintain the killing function while reducing the production of pro‐inflammatory cytokines IL‐2, IFN‐γ and TNFα, 26 which were found to be associated with CD25 + PD‐1 + T cells in this study.…”
Section: Discussionmentioning
confidence: 45%
“…The molecular mechanism underlying the distinction between the cytolytic and pro‐inflammatory function of T cells is not fully understood. However, a recent study revealed that the alternation of TCR signalling via modulating CD3 subunits can maintain the killing function while reducing the production of pro‐inflammatory cytokines IL‐2, IFN‐γ and TNFα, 26 which were found to be associated with CD25 + PD‐1 + T cells in this study.…”
Section: Discussionmentioning
confidence: 45%
“…E-cadherin speci cally binds to the NK cell inhibitory receptor KLRG1, which might provide a better solution for NK cell inhibition 30 . A previous study used an elegant design to show that a 28EZ CAR attenuated CAR-T cell activation-induced cell death (AICD) by recapitulating natural CD3ζ dephosphorylation by tethering the CD3ε domain, leading to rapid CD3ζ dephosphorylation and reduced cytokine production 31 . This is in line with our ndings.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of the cytoplasmic domain of CD3ε with a second-generation CAR could active the anti- tumor effect of CAR-T cells. It is revealed that we could reduce cytokine production of CAR by Csk-recruiting ITAM of CD3ε and produce CAR-T persistence via p85 recruitment of the basic residue rich sequence (BRS) of CD3 (39).…”
Section: Prospectivementioning
confidence: 99%